Daratumumab plus carfilzomib: An optimistic approach in relapsed/refractory multiple myeloma - A P Dubey; Sameer Khatri; Sachin Maggo; Nilabh K Singh; Durgesh Sharma (Indian Journal of Medical and Paediatric Oncology)
Background: Although with the introduction of novel agents, clinical outcomes have significantly improved in patients of multiple myeloma (MM); however, nearly all relapse, requiring subsequent treatment. Patients who have been heavily treated for relapsed/refractory MM (RRMM) have limited options and poor survival outcomes. Carfilzomib plus daratumumab combination have been evaluated in a phase 1b study in patients of RRMM progressing after 1–3 lines of therapies including bortezomib and an immune-modulatory drug. However, data are lacking evaluating the efficacy of this combination in RRMM patients who have progressed or have suboptimal response on either of these drugs (carfilzomib or daratumumab). Methods: Prospective analysis of data of 19 RRMM patients who progressed after multiple lines of therapy (including bortezomib and lenalidomide/pomalidomide) and had suboptimal response/stable/progressive disease after receiving carfilzomib or daratumumab based combination as last therapy. All patients received combination of carfilzomib plus daratumumab along with dexamethasone (DKd) after prior consent. Daratumumab (16 mg/kg IV) was administered weekly (days 1, 8, 15, and 22) during cycles 1 and 2, every 2 weeks (days 1 and 15) during cycles 3–6, and every 4 weeks thereafter. Carfilzomib was administered weekly on days 1, 8, and 15 of each 28-day cycle. Patients received an initial carfilzomib dose of 20 mg/m2 on day 1,2; 27 mg/m2 on day 8, 9, 15, 16 of cycle 1, which increased to 70 mg/m2 on day 1, 8, 15 from cycle 2 onwards if deemed tolerable. Dexamethasone was given as fixed-dose of 40 mg weekly. Results: Eighteen of 19 patients (including 3 high risk cytogenetics) to DKd (CR-4, very good partial response-10, partial response-02). After median follow-up of 16 months, progression-free survival (PFS) was 95%. Median PFS was not reached. Three patients who were transplant eligible received high-dose chemotherapy followed by autologous stem-cell transplantation and achieved minimal residual disease negativity. The most frequent all grade side effects were hematological, which included neutropenia 30%, anemia 70%, and thrombocytopenia 42%. Most frequent non hematological side effects were nausea 40%, vomiting, cough, respiratory tract infections, asthenia, and loss of appetite. Conclusion: Carfilzomib plus daratumumab based combination in RRMM patients has shown promising results in phase Ib study, where patients with prior exposure to either of these drugs were excluded. Our data show similar or better response of this combination in patients who had progressive disease/stable disease/minimal response to either of carfilzomib or daratumumab. This combination can be a better option in heavily treated RRMM (with prior exposure to either of carfilzomib or daratumumab) producing deeper and durable responses. A larger study may be required to prove this benefit.